The Role of Fat Grafting in Buttock Augmentation - O'Neill, Rebecca C.; Abu-Ghname, Amjed; Davis, Matthew J.; Chamata, Edward; Rammos, Charalambos K.; Winocour, Sebastian J. (Seminars in Plastic Surgery, 2020)
Autologous fat grafting is now considered the gold standard for buttock augmentation. Although a variety of techniques are currently being used by surgeons around the world, methods of fat grafting to the buttocks remain unsystematized, poorly understood, and controversial in terms of their safety and efficacy. Nonetheless, buttock augmentation by fat grafting has a satisfaction rate of 97.1%, and its mean complication rate has been estimated to be around 7 to 10%, with serious complications occurring in less than 1% of cases. Fat emboli are one such serious complication, with several reports in the literature discussing morbidity and mortality, specifically with intramuscular injection. With the increasing popularity of fat grafting for buttock augmentation, it is more important than ever to continue researching and learning to safeguard the satisfaction and safety of our patients.
Keywords: fat grafting; body contouring; buttock augmentation